2018
DOI: 10.1080/07317115.2018.1468377
|View full text |Cite
|
Sign up to set email alerts
|

Is Fear of Falling the Missing Link to Explain Racial Disparities in Fall Risk? Data from the National Health and Aging Trends Study

Abstract: These findings should inform public health fall prevention initiatives among community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…In our multivariable models, we found that FoF was independently associated with being female, white, Medicaid eligible, and having a higher BMI or more medical comorbidities. Prior investigations in older adults with and without VI also detected these associations and reported comparable effect sizes . The association between BMI and FoF in this study suggests that individuals with a higher BMI are more likely to fear falling even when they are no more likely to fall.…”
Section: Discussionsupporting
confidence: 82%
“…In our multivariable models, we found that FoF was independently associated with being female, white, Medicaid eligible, and having a higher BMI or more medical comorbidities. Prior investigations in older adults with and without VI also detected these associations and reported comparable effect sizes . The association between BMI and FoF in this study suggests that individuals with a higher BMI are more likely to fear falling even when they are no more likely to fall.…”
Section: Discussionsupporting
confidence: 82%
“…Of demographic variables, higher risks of fall worry with advancing age was expected. The lower fall worry likelihood among Black older adults is consistent with previous study findings (Singh et al, 2020). Another study also found that relative to non-Hispanic Whites, Black older adults had a 30% decreased risk of sustaining a fall and a 40% decreased risk of recurrent falls (Sun et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Hispanic older adults who fell in 2019 had a higher risk of recurrent falls in 2020-2021. Our finding of no difference in recurrent fall risks between Black and non-Hispanic White older adults significantly adds to the literature as previous studies tended to report lower fall prevalence and fall worry among Blacks (Geng et al, 2017;Singh et al, 2020;Sun et al, 2016). Our finding of higher fall risks among higher income older adults is consistent with previous study findings (Kelekar et al, 2021), although further research is needed to examine the underlying reasons for income-fall associations.…”
Section: Discussionsupporting
confidence: 88%